Parental motivation in children’s participation in pushbike sports: a descriptive study - Jannah, Rifdatul; Sulistyarto, Soni; Sudijandoko, Andun; Fikri, Muhammad Dzul (Sriwijaya Journal of Sport, 2026)
Research Objectives: Children's sports programs have increasingly garnered attention from the government and society in recent years, particularly recreational sports like pushbike, which have become increasingly popular among children. Creating a supportive environment where parents can balance motivation with proper understanding is crucial to helping children effectively internalize the drive to engage in sports. Research Objectives: This study aims to analyze the intrinsic and extrinsic motivation of parents in enrolling their children in the Academy Pushbike Jatim Pro. Methods: The method used was quantitative descriptive with a questionnaire containing 43 items distributed to 25 parent respondents. The data were analyzed descriptively using percentages to categorize motivation levels and were also presented in frequency diagrams for each category. Results: The results of the study indicate that parents' intrinsic motivation is more dominant in the high (32%) and very high (24%) categories, while extrinsic motivation is more prevalent in the low (44%) and very low (24%) categories. Overall, 32% of parents' motivation falls into the high category. Conclusion: These findings indicate the need for continuous evaluation and monitoring to develop young athletes with balanced intrinsic and extrinsic motivation. Additionally, further research is recommended to explore children's motivation directly, thereby providing a more comprehensive understanding of the factors influencing children's sports performance.